2018
DOI: 10.1007/s11136-018-1892-6
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Health-related quality of life in coronary heart disease: a systematic review and meta-analysis mapped against the International Classification of Functioning, Disability and Health

Abstract: In the original publication of the article, the surname of one of the co-authors was misspelled as 'Mpfou'. This has been updated in this correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The disease burden of CAD is usually evaluated by measuring HRQL, and the results of a longitudinal cohort study showed that approximately 26% of CAD patients experienced a significant reduction in HRQL over a 5-year period [17, 18]. Moreover, the framework developed by the International Classification of Functioning, Disability and Health demonstrated that reductions in HRQL in CAD patients involve not only physical symptoms with activity limitations but also social support, participation, and personal perception [19, 20]. Angina is the initial clinical manifestation in 25 to 50% of all CAD patients [21, 22] and has been associated with poor HRQL and depressive symptoms; individuals with angina exhibit higher scores for pain or worry relative to those observed in individuals without angina [2326].…”
Section: Discussionmentioning
confidence: 99%
“…The disease burden of CAD is usually evaluated by measuring HRQL, and the results of a longitudinal cohort study showed that approximately 26% of CAD patients experienced a significant reduction in HRQL over a 5-year period [17, 18]. Moreover, the framework developed by the International Classification of Functioning, Disability and Health demonstrated that reductions in HRQL in CAD patients involve not only physical symptoms with activity limitations but also social support, participation, and personal perception [19, 20]. Angina is the initial clinical manifestation in 25 to 50% of all CAD patients [21, 22] and has been associated with poor HRQL and depressive symptoms; individuals with angina exhibit higher scores for pain or worry relative to those observed in individuals without angina [2326].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) accounts for 31% of deaths worldwide [ 1 ], and 27% of deaths in Australia [ 2 ]. Rates of CVD incidence have a large economic impact and reduce quality of life and psychological wellbeing [ 3 ]. Meeting recommended levels of physical activity (PA) and consuming adequate amounts of fruit and vegetables reduces the risk of CVD [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, risk perception research has focused extensively on relatively simple, short-term behaviors such as screenings, vaccines, or condom usage as opposed to long-term changes in more complex behaviors (e.g., PA and diet [ 27 ]). Due to the high rates of chronic non-communicable diseases, further investigation of lifestyle risk factors such as PA, diet, and their relationship with health beliefs should be conducted [ 3 ].…”
Section: Introductionmentioning
confidence: 99%